All the mathematics you missed : - Garrity, Thomas A. (Cambridge University Press, 2002)
Garrity (mathematics, Williams College) explains the basic points and some results of the most important undergraduate topics in mathematics, emphasizing the intuitions underlying the subjects. Topics include linear algebra, vector calculus, point-set topology, differential equations, and probability theory, among other matterss. An annotated bibliography offers guidance to further reading. Intended for advanced undergraduates and beginning graduate students in mathematically based fields.